1998
DOI: 10.1046/j.1365-2648.1998.00594.x
|View full text |Cite
|
Sign up to set email alerts
|

Importance of information following myocardial infarction: a study of the self‐perceived information needs of patients and their spouse/partner compared with the perceptions of nursing staff

Abstract: A non-experimental research design using questionnaires, was undertaken to find out what information out of that commonly given following myocardial infarction (MI), patients and their spouse/partners rate as being most and least important. These results were then compared with the results obtained from nurse subjects, who were given the same instrument to complete. Eighteen subjects were recruited for each of the three subject groups. Results indicated that some congruency existed between the three groups in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
82
3
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(94 citation statements)
references
References 13 publications
7
82
3
2
Order By: Relevance
“…Several studies [19,27,28] have reported cardiac patients would like to receive information about resuming sexual activity. Indications suggest that while resuming sexual activity is a significant concern it often rates lower than medication and risk factors and resuming normal activities.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies [19,27,28] have reported cardiac patients would like to receive information about resuming sexual activity. Indications suggest that while resuming sexual activity is a significant concern it often rates lower than medication and risk factors and resuming normal activities.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, findings may be less relevant to those treated with p-PCI. Such studies show that patients recovering from MI [10,[17][18][19][20][21][22][23] and elective coronary angioplasty [24] have been reported to have 'unmet' information needs.…”
Section: Introductionmentioning
confidence: 99%
“…No studies have however, been performed where perceptions of educational needs among CPAP patients have been compared to the perceptions of healthcare personnel. Comparisons of patients and nurses have been done on patients with angina pectoris [18], myocardial infarction [19], congestive heart failure [20], cancer [21], and renal dialysis [22]. In general, the results indicated that all studied areas were perceived as important by patients as well as nurses.…”
Section: Introductionmentioning
confidence: 99%